The Effect of Organizational Citizenship Behavior (OCB) and Quality of Work Life (QWL) on The Employee Work Performance with Motivation As An Intervening Variables at Industrial affairs Of South Sumatera Province (International Journal of Scientific Research and Management (IJSRM), 2018)
Organizational Citizenship Behavior (OCB) is a new concept in terms of performance analysis that is not regulated by the organization, and a formal reward system is not taken into account, but this behavior will encourage the effectiveness and efficiency of the overall organizational function. High employee performance will also be created when Quality of Work Life (QWL) provides comfort and prosperity in the work environment, because it is consideredbe able to increase the role and contribution of employees in an organization. High work motivation will also have an impact on the better performance given by employees to achieve the goals of the institution. The purpose of this research are to find out whether or not : OCB affects work motivation, QWL affects work motivation, OCB affects employee performance, QWL affects employee performance, Work motivation affects employee performance, The effect of work motivation as a mediation of OCB to employee performance, The effect of work motivation as a mediation of the QWL to work performance.